Effect of Combined Mycophenolate and Rapamycin Treatment on Kidney Fibrosis in Murine Lupus Nephritis - Zhang, Chenzhu; Tam, Tsz Wai; Chau, Mel KM; García Córdoba, Cristina Alexandra; Yung, Susan; Chan, Tak Mao (Frontiers in Pharmacology, 2022)
Background: A significant proportion of lupus nephritis patients develop chronic kidney disease (CKD) and progressive kidney fibrosis, for which there is no specific treatment. We previously reported that mycophenolate or rapamycin monotherapy showed comparable efficacy in suppressing kidney fibrosis in a murine model of lupus nephritis through their direct action on mesangial cells. We extended our study to investigate the effect of combined mycophenolate and rapamycin treatment (MR) on kidney fibrosis in NZBWF1/J mice. Methods: Female NZBWF1/J mice with active nephritis were randomized to receive vehicle or treatment with mycophenolate (50 mg/kg/day) and rapamycin (1.5 mg/kg/day) (MR) for up to 12 weeks, and the effect of treatment on clinical parameters, kidney histology and fibrotic processes was investigated. Results: Progression of nephritis in untreated mice was accompanied by mesangial proliferation, glomerulosclerosis, tubular atrophy, protein cast formation, increased mTOR and ERK phosphorylation, and induction of TGF-beta1, IL-6, alpha-smooth muscle actin, fibronectin and collagen expression. Combined MR treatment prolonged survival, improved kidney function, decreased anti-dsDNA antibody level and ameliorated histopathological changes. The effect of combined MR treatment on kidney histology and function was comparable to that of mycophenolate or rapamycin monotherapy. In vitro studies in human mesangial cells showed that exogenous TGF-beta1 and IL-6 both induced mTOR and ERK phosphorylation and downstream fibrotic processes. Both mycophenolic acid and rapamycin inhibited inflammatory and fibrotic processes induced by TGF-beta1 or IL-6 by down-regulating mTOR and ERK phosphorylation. Conclusions: Our findings indicate that combined mycophenolate and rapamycin, at reduced dose improves kidney fibrosis in murine lupus nephritis, through their distinct effect on mTOR and ERK signaling in mesangial cells.